(untitled) (Medical Forum Monthly, 2026)
Objective: Rheology of four pulpectomy materials for primary teeth obturation was compared, and the relationship between flow behavior and 3-dimensional obturation quality on CBCT was tested. Study Design: In vitro study Place and Duration of Study: This study was conducted at the Pediatric and Preventive Dentistry Department, Sharad Pawar Dental College and Hospital, Datta Meghe Institute of Higher Education and Research (DMIHER) Sawangi (Meghe) Wardha 442001, Maharashtra, India from August 2024 to August 2025. Methods: Endoflas, Metapex, Metapaste, and Zinc Oxide-Eugenol were tested. Apparent viscosity of six samples of each material was measured with a strain-controlled rheometer following ISO 6876 standard at 2 minutes and at a later anchor point after mixing and/or extrusion. Eighty extracted primary mandibular second molars were prepared with standardized access, working length, instrumentation, irrigation, and syringe obturation with uniform technique. CBCT evaluation of obturation quality was performed 24 hours post-obturation with blinded evaluation by two independent scorers with high inter-rater agreement. One-way ANOVA for multiple means at α = 0.05 was used for statistical analysis. Results: Significantly different viscosities were measured for the four materials at both points (p<0.0001). Endoflas showed the highest initial viscosity, while ZOE showed the lowest viscosity among the tested materials. CBCT evaluation showed the highest quality of obturation with Endoflas (91%), then with Metapex (87%), ZOE (74%), and Metapaste (68%). Conclusion: Rheology of the tested pulpectomy materials for primary teeth obturation is strongly correlated with the quality of obturation, with the materials with the best rheology, Endoflas and Metapex, showing the best quality.